Genetic Insights Into Biological Mechanisms Governing Human Ovarian Ageing. Issue 11 (November 2021) - Ruth, Katherine S.; Day, Felix R.; Hussain, Jazib
Abstract : (Abstracted from Nature 2021;596:393–397) The age of reproductive senescence (age of natural menopause [ANM]) in developed countries is approximately 50–52 years; however, natural fertility ceases approximately 10 years before menopause. Societal trends have shifted with women choosing to delay childbearing to older ages, increasing the need for assisted conception technology.